The financing of alliance entrepreneurship - Hong, Jieying (Journal of Business Venturing, 2020)
It is popular nowadays for entrepreneurial firms to advance their entrepreneurship outside their boundaries through alliances. This paper studies how the financing of entrepreneurship changes in strategic alliances. We model a financially constrained entrepreneur and a deep-pocket incumbent developing an innovative product through a strategic alliance, which generates externalities on the incumbent. We find that i) in contrast to traditional theories, the entrepreneur's financial constraint can be tightened by an increase in his endowment; ii) an outside investor is introduced as a third party to deal with the free-riding agency problem; and iii) the externalities have a significant effect on the design of financial claims in the alliance contract, and the incentive-compatible financial instruments are consistent with empirical observations.